Neuronal dark matter: the emerging role of microRNAs in neurodegeneration - Goodall, Emily F.; Heath, Paul R.; Bandmann, Oliver; Kirby, Janine; Shaw, Pamela J. (Frontiers in Cellular Neuroscience, 2013)
MicroRNAs (miRNAs) are small, abundant RNA molecules that constitute part of the cell’s non-coding RNA “dark matter”. In recent years, the discovery of miRNAs has revolutionised the traditional view of gene expression and our understanding of miRNA biogenesis and function has expanded. Altered expression of miRNAs is increasingly recognised as a feature of many disease states, including neurodegeneration. Here, we review the emerging role for miRNA dysfunction in Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis and Huntington’s disease pathogenesis. We emphasise the complex nature of gene regulatory networks and the need for systematic studies, with larger sample cohorts than have so far been reported, to reveal the most important miRNA regulators in disease. Finally, miRNA diversity and their potential to target multiple pathways, offers novel clinical applications for miRNAs as biomarkers and therapeutic agents in neurodegenerative diseases.